Pengaruh Bauran Promosi, Harga, Display Produk dan Kualitas Layanan terhadap Keputusan Pembelian pada Apotek Anugerah Farma di Kota Gorontalo - Suyanto, Mohamad Afan; M, Muh Akmar; Karundeng, Deby Rita (Mabsya: Jurnal Manajemen Bisnis Syariah, 2021)
The research aims to determine the effect of: Promotion Mix on Purchasing Decisions, Prices on Purchasing Decisions, Product Display on Purchasing Decisions, Service Quality on Purchasing Decisions at Anugerah Farma Pharmacy in Gorontalo City and to determine the Effect of Promotion Mix, Price, Product Display and Service Quality on Purchasing Decision at Anugerah Farma Pharmacy in Gorontalo City This research approach is a qualitative descriptive approach. This type of research is a survey, namely analyzing the facts that support the information needed to support the research discussion, in solving and answering the main problems posed. The data were obtained through distributing questionnaires, then the data were analyzed descriptively and multiple regression analysis. The results showed that partially the promotion mix had a positive and significant effect on purchasing decisions. Price has a positive and insignificant effect on the decision. Product display has a positive and significant effect on purchasing decisions. Service quality has a positive and significant effect on purchasing decisions at Anugerah Farma Pharmacy and simultaneously the promotion mix, price, product display and service quality have a positive and significant effect on purchasing decisions at Anugerah Farma Pharmacy, Gorontalo City.